The Effect Of Financial Literacy, Self-Management And Use Of Financial Technology On Financial Readiness Through Self-Competency As An Intervening Variable On Students Of The Faculty Of Economics And Business, State University Of Makassar - Muliana; Syamsu Rijal; Ika Wisudawaty; Nurjannah; Andi Caezar To Tadampali (International Journal of Business and Quality Research, 2026)
The purpose of this study was to understand the influence of financial literacy, self-management, and the use of financial technology on financial readiness, with self-competence acting as an intervening variable in students at the Faculty of Economics and Business, Makassar State University. The approach used was quantitative with a descriptive research type. The study population included 2,550 active students from the 2022 and 2023 intakes at the faculty, with a sample of 346 respondents. Data were collected through a structured questionnaire and analyzed using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method. The results showed that financial literacy, self-management, and the use of financial technology had a positive and significant influence on students' self-competence, which in turn was shown to have a positive and significant influence on their financial readiness. Self-competence was shown to act as a significant intervening variable in the relationship between financial literacy, self-management, and the use of financial technology on students' financial readiness.